Towards the Compatibility of Professional and Scientific Learning Outcomes: Insights and Options in the Context of Competence Orientation - Rein, Volker (International Journal for Research in Vocational Education and Training, 2017)
The steady increase in science-related requirements in operational areas of skilled and managing workforce is influencing worldwide the discourse on shaping professionalization. This article focuses on the compatibility of professional and scientific competence-oriented learning outcomes of qualification programmes within and across the education and training sectors. It is assumed that there is not, per se, a conceptual dichotomy in designing education and training programmes and credentials in a competence-oriented manner to address complex professional and scientific requirements in education and training in a compatible way. The article tries to shift the discussion from a systemic and institutional focus to a conceptual- and requirement-oriented perspective on qualification design. Using Germany as an example, it discusses the conceptual intersections of Vocational Education and Training and academic Higher Education on competence, and comparatively analyzes competence-oriented instruments for the classification and the transparency of learning outcomes and their application in the education practice of dual study programmes with vocational reference qualifications. On this basis, the article elucidates identified characteristics of comprehensive professional-scientific competences and relevant requirement areas in education and training. In addition, further prerequisites for an integrated competence acquisition in education programmes are discussed as well. It is assumed that these characteristics can also be regarded as important prerequisites for the connectivity of qualifications and permeable pathways within and between education systems.